2018
DOI: 10.3390/cryst8110421
|View full text |Cite
|
Sign up to set email alerts
|

Optical Detection of Green Emission for Non-Uniformity Film in Flat Panel Displays

Abstract: Among colours, the green colour has the most sensitivity in human vision so that green colour defects on displays can be effortlessly perceived by a photopic eye with the most intensity in the wavelength 555 nm of the spectrum. With the market moving forward to high resolution, displays can have resolutions of 10 million pixels. Therefore, the method of detecting the appearance of the panel using ultra-high resolutions in TFT-LCD is important. The machine vision associated with transmission chromaticity spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The image perception is quite critical in the display as human vision is so sensitive. Thus, image quality needs to be more precious than just noticeable difference (JND) [ 16 , 17 ]. However, human vision does not have only scientifically quantitative properties but also objective properties.…”
Section: Principles Of the Automatic Optical Inspection For Tftmentioning
confidence: 99%
See 2 more Smart Citations
“…The image perception is quite critical in the display as human vision is so sensitive. Thus, image quality needs to be more precious than just noticeable difference (JND) [ 16 , 17 ]. However, human vision does not have only scientifically quantitative properties but also objective properties.…”
Section: Principles Of the Automatic Optical Inspection For Tftmentioning
confidence: 99%
“…Within the photosensor industry, time delay and integration (TDI) is a scanning device that increases the sensitivity of the multiple line-scan [ 17 ]. TDI-CCD has an area array structure but has a linear array.…”
Section: Principles Of the Automatic Optical Inspection For Tftmentioning
confidence: 99%
See 1 more Smart Citation
“…The defect in LCD can be detected by the human eye as it can perceive green light of spectrum 555 nm. Tzu, F. -M., et al [8] demonstrated machine vision associated with transmission chromaticity spectrometer to detect non-uniformity of the green emission layer for TFT-LCD. The just noticeable difference was utilized as the detection criterion, according to that of the International Commission on Illumination.…”
mentioning
confidence: 99%